Perioperative pain management and opioid‐reduction in head and neck endocrine surgery: An American Head and Neck Society Endocrine Surgery Section consensus statement. Issue 8 (3rd June 2021) - Ferrell, Jay K.; Shindo, Maisie L.; Stack, Brendan C.; Angelos, Peter; Bloom, Gary; Chen, Amy Y.; Davies, Louise; Irish, Jonathan C.; Kroeker, Teresa; McCammon, Susan D.; Meltzer, Charles; Orloff, Lisa A.; et al.
Abstract: Background: This American Head and Neck Society (AHNS) consensus statement focuses on evidence‐based comprehensive pain management practices for thyroid and parathyroid surgery. Overutilization of opioids for postoperative pain management is a major contributing factor to the opioid addiction epidemic however evidence‐based guidelines for pain management after routine head and neck endocrine procedures are lacking. Methods: An expert panel was convened from the membership of the AHNS, its Endocrine Surgical Section, and ThyCa. An extensive literature review was performed, and recommendations addressing several pain management subtopics were constructed based on best available evidence. A modified Delphi survey was then utilized to evaluate group consensus of these statements. Conclusions: This expert consensus provides evidence‐based recommendations for effective postoperative pain management following head and neck endocrine procedures with a focus on limiting unnecessary use of opioid analgesics.